Large Spin‐to‐Charge Conversion at Room Temperature in Extended Epitaxial Sb2Te3 Topological Insulator Chemically Grown on Silicon. (15th October 2021) - Longo, Emanuele; Belli, Matteo; Alia, Mario; Rimoldi, Martino; Cecchini, Raimondo; Longo, Massimo; Wiemer, Claudia; Locatelli, Lorenzo; Tsipas, Polychronis; Dimoulas, Athanasios; Gubbiotti, Gianluca; Fanciulli, Marco; et al.
Abstract: Spin‐charge interconversion phenomena at the interface between magnetic materials and topological insulators (TIs) are attracting enormous interest in the research effort toward the development of fast and ultra‐low power devices for future information and communication technology. A large spin‐to‐charge (S2C) conversion efficiency in Au/Co/Au/Sb2 Te3 /Si(111) heterostructures based on Sb2 Te3 TIs grown by metal–organic chemical vapor deposition on 4″ Si(111) substrates is reported. By conducting room temperature spin pumping ferromagnetic resonance, a 250% enhanced charge current due to spin pumping in the Sb2 Te3 ‐containing system is measured when compared to the reference Au/Co/Au/Si(111). The corresponding inverse Edelstein effect length λIEE ranges from 0.28 to 0.61 nm, depending on the adopted methodological analysis, with the upper value being so far the largest observed for the second generation of 3D chalcogenide‐based TIs. These results open the path toward the use of chemical methods to produce TIs on large area Si substrates and characterized by highly performing S2C conversion, thus marking a milestone toward future technology‐transfer. Abstract : By conducting room temperature spin pumping ferromagnetic resonance, a high spin‐to‐charge conversion occurring in the large area Sb2 Te3 topological insulator epitaxially grown by metal–organic chemical vapor deposition on 4″ Si(111) is demonstrated. An inverse Edelstein effect length λIEE in the range of 0.28–0.61 nm is measured, which opens viable routes toward the future technology‐transfer of chemically produced topological insulators.